The Effect of Organizational Culture and Job Satisfaction on Employee Performance at Manufacturing Companies - Tiana Candra; Nur Firdaus Fitra Suprapto; Muhamad Alwi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study seeks to determine how employee performance at Manufacturing Companies in Cirebon is affected by organizational culture and job satisfaction. Descriptive correlation research using quantitative techniques is the methodology used in this study. All 100 employees of Manufacturing Companies in Cirebon constituted the study population, which was selected using a direct random sampling technique. Employee performance, job satisfaction, and organizational culture questionnaires provided the data. Multiple linear regression analysis is the method used to analyze the data in this study. Based on the results of Multiple Linear Regression analysis with t-test and F-test, this study concludes that employee performance is influenced by organizational culture within Manufacturing Companies in Cirebon. Job satisfaction affects the performance of Manufacturing Companies in Cirebon employees. Job satisfaction and organizational culture affect the performance of Manufacturing Companies in Cirebon employees. Organizational culture and job satisfaction affect employee performance at Manufacturing Companies in Cirebon by 29.8%.